The Evaluation of Difficulties in the Sense of Pre - Service Teachers That are Encountered in the Teaching Practice Lesson in the Div ision of Mentally Retarded Teacher Training Programme - Selahattin Avşaroğlu; Bekir Bural (Mehmet Tekerek, 2012)
The aim of this research is to evaluate the difficulties in the sense of teacher candidates that are experienced by students, who are enrolled in the Mentally Retarded Teacher Training Depar tment, in teaching application courses. For this purpose, in the academic year 2009 - 2010, thirty eight (38) last year students, training in seven primary schools and in the educational practice school situated in the centre of Konya province were intervi ewed. In the survey, data were obtained with the semi structured interviews. The interviews were recorded with the tape recorder and the data transcripts were analyzed with the help of content analysis method. According to the research findings, the interv iewed teachers stated that their supervisor teachers did not guide them sufficiently, and they experienced defects in explaining and instructing school and classroom rules, and in practice of training activities and sharing information with others are dete rmined. Additionally, nearly half of the student teachers had problems in interacting with supervisor teachers, and the student teachers stated that there were a large amount of material deficiencies in schools and classrooms.